#### Answer

g = 1

#### Work Step by Step

(g + 4) - 3g = 1 + g
To get the variable (g) on one side of the equation, add 3g to both sides of the equation.
(g + 4) - 3g + 3g = 1 + g + 3g
Simplify and combine like terms.
g + 4 = 1 + 4g
Subtract g from both sides of the equation to eliminate g from the left side of the equation.
g + 4 - g = 1 + 4g - g
4 = 1 + 3g
Subtract 1 from both sides of the equation.
4 - 1 = 1 + 3g - 1
Simplify to get:
3 = 3g
Divide both sides by 3:
$\frac{3}{3}$ = $\frac{3g}{3}$
1 = g
Check:
To check whether 1 is the correct answer, replace g with 1 in the original equation and solve.
(g + 4) - 3g = 1 + g
(1 + 4) - 3(1) = 1 + 1
5 - 3 = 1 + 1
2 = 2